2017
DOI: 10.20961/jpscr.v2i02.11040
|View full text |Cite
|
Sign up to set email alerts
|

Aktivitas Antioksidan Buah Kopi Hijau Merapi

Abstract: Coffee favored because it has flavor, distinctive aroma, and contain bioactive components that can act as an antioxidant. This study aims to determine the antioxidant activity of extracts and fractions of green coffee cherries of Merapi. Green coffee cherries macerated with chloroform further partitioned with 80% methanol solvent. Measurement of antioxidant activity using DPPH spectrophotometric method. The results showed the chloroform extract has antioxidant activity 2.21 mg / mL, the methanol soluble 1.88 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
3
0
5
Order By: Relevance
“…Desai et al (2019) cover the antioxidant compounds of green coffee using the 12.78 µg/ mL microencapsulation method, the results are lower than that in this study. This was higher than that of Bobková et al (2020), which stated that low-quality roasted green coffee powders are about 69.08-78.55 µg/mL and Isnindar et al (2017). Masek et al (2020) reported that robusta coffee and robusta green coffee contain antioxidants with an IC 50 of 2210 µg/mL and 81.6 µg/ mL, respectively.…”
Section: Antioxidant Activitymentioning
confidence: 65%
“…Desai et al (2019) cover the antioxidant compounds of green coffee using the 12.78 µg/ mL microencapsulation method, the results are lower than that in this study. This was higher than that of Bobková et al (2020), which stated that low-quality roasted green coffee powders are about 69.08-78.55 µg/mL and Isnindar et al (2017). Masek et al (2020) reported that robusta coffee and robusta green coffee contain antioxidants with an IC 50 of 2210 µg/mL and 81.6 µg/ mL, respectively.…”
Section: Antioxidant Activitymentioning
confidence: 65%
“…Penentuan waktu inkubasi dilakukan dengan tujuan untuk mengetahui waktu maksimal saat nilai absorbansi stabil dari reaksi antara reagen dengan sampel (Isnindar et al, 2017).…”
Section: Pembacaan Panjang Gelombang Dan Waktu Inkubasiunclassified
“…Panjang gelombang maksimal dari pengukuran didapatkan 750 nm. Penentuan dua parameter dilakukan untuk memastikan kestabilan reaksi (Isnindar et al, 2017) dan panjang gelombang maksimum memberikan sensitivitas yang baik (Putri et al, 2022). Hasil penentuan kurva baku didapatkan persamaan regresi linier yaitu y = 3,38x + 0,7396 dengan nilai r = 0,997 (Gambar 1).…”
Section: Penetapan Kurva Baku Albuminunclassified